Psoriasis and biological drugs at the time of SARS-CoV-2 infection: a mini review outlining risk of infection, seroprevalence, and safety and efficacy of the BNT162b2 vaccine - Railton, Janosch; Volonté, Martina; Isoletta, Eugenio; Bonelli, Alice; Barruscotti, Stefania; Brazzelli, Valeria (Frontiers in Immunology, 2024)
The aim of this study is to review the life of psoriatic patients on biologic therapy during the SARS-CoV-2 pandemic and the relevance of frailty within this context, reviewing studies which describe the course and severity of infection in psoriatic patients on biologics, the seroprevalence of SARS-CoV-2, and the safety and efficacy of the BNT162b2 vaccine in these patients.The keywords "Psoriasis", "Biologics", "SARS-CoV-2", "COVID-19" and "BNT162b2 Vaccine" were used in various combinations on database engines to find relevant articles on this topic.Results: A total of 36 articles were found, 20 concerning the course, severity and seroprevalence of SARS-CoV-2 in psoriatic patients on biologic therapy, and 16 concerning safety and efficacy of BNT162b2 in these patients.Discussion: Psoriatic patients on biologic therapy did not have increased seroprevalence compared to the general population, indicating that they were not at an increased risk of SARS-CoV-2 infection compared to the general population. Furthermore, the immunosuppressive action of biologics may be protective, as patients on biologic therapy had better outcomes and less risk of severe infection. The seroconversion rate against SARS-CoV-2 from the BNT162b2 vaccine was similar in both psoriatic patients on biologics and the general population, indicating efficacy is not hindered by the biologic therapy. However, the cellular response in in psoriatic population was significantly less intense, and the humoral immune response was weaker than in the general population, demonstrating that the possibility of tighter vaccination schedules and additional doses may be advantageous in these patients.